Organizational factors associated with internal customer satisfaction :a case study in retail business - Wong, Siew Harng (Universiti Malaysia Sarawak, UNIMAS, 2009)
The purpose of this study was to determine the organizational factors that associated with internal customer satisfaction at H&L Supermarket Sdn Bhd. The dependent variable in this study was the internal customer satisfaction meanwhile the independent variables were wages, work itself, supervisory support and co-worker. Survey methodologies, a questionnaire in a form of Likert Scale were used to obtain data. 261 respondents were successfully selected as a sample from an overall population of 325 employees. The data collected was analyzed using the Statistical Package for the Social Sciences (SPSS), Version 15.0. Percentages were used to determine the distribution of demography. Pearson correlation analysis had been used to determine the organizational factors. Simple Regression Analysis was used to determine dominant factor in affecting the internal customer satisfaction. The finding shows that the level of internal customer satisfaction in H&L Supermarket Sdn Bhdwas considered as high. The findings also showed significant level of correlation between independent variables (wages, work itself, supervisory support and co-workers)and dependent variable (internal customer satisfaction). It was also found that all the organizational factors namely wages, work itself, supervisory support and co-workers were the dominant factors that influences the internal customer satisfaction. As a conclusion, the internal customer was affected by the wages, work itself, supervisory support and co-worker . The findings of this study can be used as a reference in improving internal customer or employee satisfaction from time to time.